Prognostic value of the combined fibrinogen and prognostic nutritional index score in resectable gastric cancer - Lin, Shuxiang; Zheng, Changyue; Chen, Zehui; Chen, Yulin; Lin, Wei (Frontiers in Oncology, 2025)
ObjectiveThis study aimed to evaluate the prognostic value of the preoperative fibrinogen and prognostic nutritional index (PNI) combination score (F-PNI) in predicting long-term survival following radical gastrectomy in patients diagnosed with resectable gastric cancer.MethodsA retrospective cohort analysis was performed using clinicopathological and follow-up data from 491 patients who underwent radical gastrectomy for gastric cancer at a single tertiary institution between January 2012 and December 2017. Statistical analyses were conducted using SPSS version 25.0 to identify independent prognostic factors associated with five-year overall survival.ResultsThe optimal preoperative cut-off values were identified as 3.335 mg/L for fibrinogen and 52.7 for the PNI. The area under the receiver operating characteristic curve (AUC) for the F-PNI score was 0.633, demonstrating higher discriminative ability compared to PNI alone (AUC = 0.592) and fibrinogen alone (AUC = 0.587). Kaplan–Meier survival analysis showed five-year survival rates as follows: low vs. high fibrinogen levels, 72.9% vs. 56.4%; high vs. low PNI, 82.6% vs. 58.0%; and F-PNI score 0, 1, and 2, 87.8%, 66.9%, and 50.0%, respectively. Both univariate and multivariate Cox proportional hazards models identified a high F-PNI score, advanced age, pathological TNM stage IIIA–IIIC, and vascular invasion as independent prognostic factors for five-year survival. The F-PNI score demonstrated superior prognostic performance compared to either fibrinogen or PNI alone.ConclusionThe F-PNI combination score is an independent prognostic marker for long-term survival in patients undergoing radical resection for resectable gastric cancer. Its enhanced predictive accuracy relative to fibrinogen or PNI individually suggests potential utility in preoperative prognostic stratification.